Import substitution policy in Russia under conditions of overcoming external sanction pressure - M. V. Shatokhin; T. G. Antropova; N. M. Surai; E. N. Sepiashvili (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to revealing the role of import substitution policy in the development of the domestic market. The article examines foreign approaches to the implementation of import substitution. The analysis of the main groups in the commodity structure of Russian imports for the period 2017–2021 is carried out. The results of import substitution of the main commodity groups of imports for the period 2014–2021 are considered. Problems and obstacles in the production of domestic goods are identified. Scenarios for the development of the importsubstituting policy of the state are predicted. The article outlines the priority areas of import substitution policy in Russia.